Loess stratigraphy using palaeomagnetism: application to the Poiana Cireşului archaeological site (Romania) - Zeeden, Christian; Hambach, Ulrich; Steguweit, Leif; Anghelinu, Mircea (Quaternary international, 2010)
Palaeomagnetic investigations were carried out at the archaeological site of Poiana Cireşului (Romania) to check whether the loess records a reliable palaeomagnetic signal, and to compare this signal to reference data. The sediments are composed of loess and loess-like sediments. Pedogenic alterations and a pronounced cultural layer occur in the section. The archaeology-bearing sedimentary geoarchive spans the time interval from ca. 20 to ca. 55 ka, and was dated mainly by 14C and luminescence techniques. The record of geomagnetic palaeosecular variation from this European loess site is discussed. The presented palaeomagnetic record bears analogies to data from Lac du Bouchet (France), and is a reliable high resolution record (mean sedimentation rates are ca. 20 cm/ky) of palaeosecular variation. The results imply that European loess geoarchives may record palaeosecular variation features, even if loess is (pedogenically) altered. The palaeosecular variation pattern of loess is here employed as a stratigraphic too